PW 2287 Efficacy of head and torso rewarming using a human model for severe hypothermia. (November 2018) - Giesbrecht, Gordon; McDonald, Gerren
Abstract : Background: Up to 10% of all drownings in western industrialized nations, occur in submerged vehicles (e.g., 350–400/year in North America). Most passenger vehicles are inherently stable in the upright position and will float for about one minute before water rises against the side windows, preventing them from opening. It is especially tragic that victims are often uninjured and functional, yet they are found with windows still closed and sometimes even with their seatbelts still on. A survey on vehicle submersion indicates that many people are not yet aware of the SWOC protocol. Method: Traditionally, emergency dispatch protocols for calls to 9–1–1 have focused on determining the location of the sinking vehicle and instructing the occupants to wait in the vehicle for rescue; this is inadequate because response times are longer than the one minute in which occupants can get out of the vehicle. Therefore, two new protocols were developed for vehicles 'sinking in water' and 'stranded in floodwater'. Both protocols immediately instruct the caller to follow the SWOC protocol. These protocols are currently available in about 60% of the English-speaking world and have been translated into several other languages. Results: To our knowledge, this protocol was successfully used for the first time by Collier County Sheriff's Office (Florida) in January, 2018. A woman, with a small child in a car seat, accidentally drove her vehicle into a canal and called 9–1–1. The operator immediately instructed the woman to follow the SWOC protocol. The driver followed instructions and both occupants survived. Implications: Knowledge and practice of the SWOC protocol is a key component to surviving a vehicle submersion incident. While efforts should continue to educate the general public regarding SWOC, there is a clear value to having this procedure included in all emergency dispatch protocols for vehicle submersion. Funding: NSERC, Canada.